Increased frequency of de novo copy number variants in congenital heart disease by integrative analysis of single nucleotide polymorphism array and exome sequence data. - Glessner, Joseph T; Bick, Alexander G; Ito, Kaoru; Homsy, Jason; Rodriguez-Murillo, Laura; Fromer, Menachem; Mazaika, Erica; Vardarajan, Badri; Italia, Michael; Leipzig, Jeremy; DePalma, Steven R; Golhar, Ryan; et al. (Circ Res, 2014)
RATIONALE: Congenital heart disease (CHD) is among the most common birth defects. Most cases are of unknown pathogenesis. OBJECTIVE: To determine the contribution of de novo copy number variants (CNVs) in the pathogenesis of sporadic CHD. METHODS AND RESULTS: We studied 538 CHD trios using genome-wide dense single nucleotide polymorphism arrays and whole exome sequencing. Results were experimentally validated using digital droplet polymerase chain reaction. We compared validated CNVs in CHD cases with CNVs in 1301 healthy control trios. The 2 complementary high-resolution technologies identified 63 validated de novo CNVs in 51 CHD cases. A significant increase in CNV burden was observed when comparing CHD trios with healthy trios, using either single nucleotide polymorphism array (P=7×10(-5); odds ratio, 4.6) or whole exome sequencing data (P=6×10(-4); odds ratio, 3.5) and remained after removing 16% of de novo CNV loci previously reported as pathogenic (P=0.02; odds ratio, 2.7). We observed recurrent de novo CNVs on 15q11.2 encompassing CYFIP1, NIPA1, and NIPA2 and single de novo CNVs encompassing DUSP1, JUN, JUP, MED15, MED9, PTPRE SREBF1, TOP2A, and ZEB2, genes that interact with established CHD proteins NKX2-5 and GATA4. Integrating de novo variants in whole exome sequencing and CNV data suggests that ETS1 is the pathogenic gene altered by 11q24.2-q25 deletions in Jacobsen syndrome and that CTBP2 is the pathogenic gene in 10q subtelomeric deletions. CONCLUSIONS: We demonstrate a significantly increased frequency of rare de novo CNVs in CHD patients compared with healthy controls and suggest several novel genetic loci for CHD.
Keywords: Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Exome; Gene Frequency; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Molecular Sequence Data; Polymorphism, Single Nucleotide

De novo mutations in histone-modifying genes in congenital heart disease. - Zaidi, Samir; Choi, Murim; Wakimoto, Hiroko; Ma, Lijiang; Jiang, Jianming; Overton, John D; Romano-Adesman, Angela; Bjornson, Robert D; Breitbart, Roger E; Brown, Kerry K; Carriero, Nicholas J; Cheung, Yee Him; et al. (Nature, 2013)
Congenital heart disease (CHD) is the most frequent birth defect, affecting 0.8% of live births. Many cases occur sporadically and impair reproductive fitness, suggesting a role for de novo mutations. Here we compare the incidence of de novo mutations in 362 severe CHD cases and 264 controls by analysing exome sequencing of parent-offspring trios. CHD cases show a significant excess of protein-altering de novo mutations in genes expressed in the developing heart, with an odds ratio of 7.5 for damaging (premature termination, frameshift, splice site) mutations. Similar odds ratios are seen across the main classes of severe CHD. We find a marked excess of de novo mutations in genes involved in the production, removal or reading of histone 3 lysine 4 (H3K4) methylation, or ubiquitination of H2BK120, which is required for H3K4 methylation. There are also two de novo mutations in SMAD2, which regulates H3K27 methylation in the embryonic left-right organizer. The combination of both activating (H3K4 methylation) and inactivating (H3K27 methylation) chromatin marks characterizes 'poised' promoters and enhancers, which regulate expression of key developmental genes. These findings implicate de novo point mutations in several hundreds of genes that collectively contribute to approximately 10% of severe CHD.
Keywords: Adult; Case-Control Studies; Child; Chromatin; DNA Mutational Analysis; Enhancer Elements, Genetic; Exome; Female; Genes, Developmental; Heart Diseases; Histones; Humans; Lysine; Male; Methylation; Mutation; Odds Ratio; Promoter Regions, Genetic